Democratisation and Institutional Reform in Albania - Gjevori, Elvin (New Perspectives on South-East Europe,, 2018)
Albania's democratic transition - one of the longest and most arduous of post-communist Europe - has failed to produce consolidated institutions. Therefore, this book undertakes the first comprehensive review of Albania's military and judicial reform - from 1992 to 2009 - to ascertain why military reform produced substantial institutionalisation and judicial reform did not. The author analyses the different outcomes by outlining how political elites constructed the interests that shaped their subsequent political actions. Overall, this book presents a novel theoretical account for institutionalisation in emerging democracies and sheds light on two of Albania's most important democratisation reforms. The book will appeal to practitioners working on institutionalisation reforms, institutionalist and democratisation researchers interested in post-authoritarian transitions, and area study scholars focusing on Albania and the Western Balkans.